Analysis on training effects of postural control for elderly adults - Piao, Yong-Jun; Kim, Kyung; Yu, Mi; Kwon, Tae-Kyu; Kim, Dong-Wook; Kim, Nam-Gyun (International journal of precision engineering and manufacturing, 2009)
In this study, we describe the effects of a training system based on an unstable platform and a visual interactive system in improving the postural control ability. In order to verify the training effects, fifteen elderly volunteers took part in a series of balance training using this system. An additional fifteen elderly volunteers which were employed as the control group, were also tested for comparison with the training group. To evaluate the effects of the training, we measured the relevant parameters, such as the sway path and the sway area of center of pressure in the different visual conditions and standing positions, the concentric isokinetic strength of ankle and knee joints prior to and after the training. The results indicated that the training system could be used to assess successfully the gradual improvement of the postural control capability of the volunteers in the system, and showed promise in terms of improving the balance capabilities of the volunteers. Moreover, the observed significant improvement in the postural capability of the elderly subjects indicated that elderly subjects may benefit more from training using the system described herein for the improvement of postural control ability.